(untitled) (Bangladesh Journal of Botany, 2022)
Experiments were conducted at Research Farm of Agromet Research Centre, SKUAST-Jammu, during rabi 2015-16 and 2016-17, and comprised of 3 varieties, 3 sowing environments and 3 N-levels laid out in split-split plot design. The growth and development of wheat crop was also validated through CERES-Wheat model. Earlier sown wheat took more days for physiological maturity as compared to normal and late sown crop. WH-1105 variety took maximum days for physiological maturity and followed by HD-2967 and RSP- 561. Higher dose of nitrogen took more calendar days for physiological maturity as compared to lower doses of nitrogen. WH 1105 variety recorded significantly superior grain and biological yield as compared to HD 2967 and RSP 561. The coefficient of determination (R2) between validation of observed and simulated days to anthesis and maturity was 0.79 and 0.76, respectively. The values obtained for R2 during validation of CERES-wheat model for grain yield of wheat was 0.78. Maximum temperature during reproductive stage showed distinct effect on grain yield of crop. Bangladesh J. Bot. 51(4): 759-765, 2022 (December)